2003
DOI: 10.1083/jcb.200211118
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species as essential mediators of cell adhesion

Abstract: Signal transduction by reactive oxygen species (ROS; “redox signaling”) has recently come into focus in cellular biology studies. The signaling properties of ROS are largely due to the reversible oxidation of redox-sensitive target proteins, and especially of protein tyrosine phosphatases, whose activity is dependent on the redox state of a low pKa active site cysteine. A variety of mitogenic signals, including those released by receptor tyrosine kinase (RTKs) ligands and oncogenic H-Ras, involve as a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
197
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(212 citation statements)
references
References 46 publications
12
197
0
Order By: Relevance
“…One of the identified downstream targets of ROS is tyrosine phosphatases. ROS cause oxidation of cysteine residues in the tyrosine phosphatase catalytic domain to form a disulfide bond, resulting in the inactivation of tyrosine phosphatases (37)(38)(39)(40)(41). Whether inactivation of tyrosine phosphatases is one of the underlying mechanisms whereby xanthine oxidase-dependent ROS production mediates activation of SRC tyrosine kinases remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…One of the identified downstream targets of ROS is tyrosine phosphatases. ROS cause oxidation of cysteine residues in the tyrosine phosphatase catalytic domain to form a disulfide bond, resulting in the inactivation of tyrosine phosphatases (37)(38)(39)(40)(41). Whether inactivation of tyrosine phosphatases is one of the underlying mechanisms whereby xanthine oxidase-dependent ROS production mediates activation of SRC tyrosine kinases remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have also demonstrated that ROS mediate leukocytes' recruitment to wounded areas [47][48][49][50]. It has been shown that the Lyn kinase is activated by wound-generated H 2 O 2, inducing the chemotactic movement of leukocytes [51].…”
Section: Introductionmentioning
confidence: 99%
“…Racdependent redox signals have an established role not only in cell proliferation and survival (Joneson and BarSagi, 1998;Bedogni et al, 2003), but also in adhesion, detachment and shape changes, secretion of metalloproteases and epithelial-mesenchimal transition (Kheradmand et al, 1998;Werner and Werb, 2002;Chiarugi et al, 2003;Radisky et al, 2005), all responses integral to the invasive and metastatic behavior of malignant cells; activation of the Rac-ROS cascade by c-Met therefore appears to be biologically plausible. Interestingly, a redox-sensitive component has been recently identified in the signaling pathway triggered by plexins (Ventura and Pelicci, 2002), a family of molecules known to associate and cooperate with c-Met during invasive growth .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several PTPs have been previously reported to associate with the HGF/SF receptors (VillaMoruzzi et al, 1998;Maroun et al, 2000;Palka et al, 2003) and to modulate its downstream signaling pathways. Moreover, preliminary evidence suggests physical association between c-Met and the low molecular weight protein tyrosine phoshatase (LMW-PTP; data not shown), an enzyme exquisitely sensitive to redox modulation by growth factors and integrins (Chiarugi et al, 2003;Nimnual et al, 2003), and able to restrain ligand-dependent activation of MAP kinases (Chiarugi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation